A Bioinspired Iron‐Molybdenum μ‐Nitrido Complex and Its Reactivity toward Ammonia Formation. Issue 30 (7th June 2022) - Su, Linan; Yang, Dawei; Jiang, Yang; Li, Yahui; Di, Kai; Wang, Baomin; Ye, Shengfa; Qu, Jingping
Abstract: Multimetallic nitride species, especially those containing biologically related iron or molybdenum, are fundamentally important to understand the nitrogen reduction process catalysed by FeMo‐nitrogenase. However, until now, there remains no report about the construction of structurally well‐defined FeMo heteronuclear nitrido complex and its reactivity toward ammonia formation. Herein, a novel thiolate‐bridged Fe II Mo VI complex featuring a bent Fe−N≡Mo fragment is synthesized and structurally characterized, which can be easily protonated to form a μ ‐ imido complex. Subsequently, through the proton‐coupled electron transfer (PCET) process, this imido species can smoothly convert into the μ ‐ amido complex, which can further undergo reductive protonation to afford the FeMo complex containing an ammine ligand. Overall, we present the first well‐defined {Fe(μ‐S)2 Mo} platform that can give a panoramic picture for the late stage (N 3− →NH 2− →NH2 − →NH3 ) of biological nitrogen reduction by the heterometallic cooperativity. Abstract : The first example of a thiolate‐bridged iron‐molybdenum μ‐nitrido complex allows the stepwise transformation of N 3− →NH 2− →NH2 − →NH3 in which all the key intermediates are isolated and well‐characterized. It offers a unique perspective into the heterometallic cooperativity in the FeMo‐cofactor.